Screening of New Potential Probiotics Strains against Photobacterium damselae Subsp. piscicida for Marine Aquaculture - Gutiérrez Falcón, Ana (Animals (Basel), 2021)
SIMPLE SUMMARY: Marine aquaculture has been one of the fastest growing animal production sectors in the last thirty years worldwide. On intensive farms, 10% of the population dies exclusively from pathogen activity, and Photobacterium damselae subsp. piscicida is one of the major infectious agents causing marine fish mortality. The purpose of this study is to obtain potential probiotic strains against pasteurellosis, in order to limit the use of chemotherapy, avoiding the environmental impact generated by the abusive use of these products. Bacterial strains isolated from different fish species were characterized in vitro and in vivo to determine their probiotic properties. Of the total number of strains isolated, only one showed excellent results to continue its characterization in vivo against this marine pathogen. The use of this strain as a possible probiotic for marine aquaculture will be in progress in future studies. ABSTRACT: On intensive fish farms, 10% of the population dies exclusively from pathogens, and Photobacterium damselae subsp. Piscicida (Ph. damselae subsp. Piscicida), the bacteria causing pasteurellosis in marine aquaculture, is one of the major pathogens involved. The objective of this study was to obtain new probiotic strains against pasteurellosis in order to limit the use of chemotherapy, avoiding the environmental repercussions generated by the abusive use of these products. In this study, 122 strains were isolated from the gills and intestines of different marine fish species and were later evaluated in vitro to demonstrate the production of antagonistic effects, the production of antibacterial substances, adhesion and growth to mucus, resistance to bile and resistance to pH gradients, as well as its harmlessness and the dynamic of expression of immune-related genes by real-time PCR after administration of the potential probiotic in the fish diet. Only 1/122 strains showed excellent results to be considered as a potential probiotic strain and continue its characterization against Ph. damselae subsp. piscicida to determine its protective effect and elucidating in future studies its use as a possible probiotic strain for marine aquaculture.